Optimalisasi Keamanan Data Pada Sistem Operasi Windows Melalui Penerapan Teknologi Kriptografi Modern - Rakhmadi Rahman; Mulyadi Mulyadi; Alif Imran (Universitas Katolik Widya Karya Malang, 2024)
Data security is an important aspect of information systems, especially in the widely used windows operating system environment. Modern encryption technology offers a variety of ways to increase data protection from security threats. This method utilizes literature insights and comparative analysis of various cryptographic techniques applied to the Windows operating system. Data sources were obtained from academic journals, books and technical documents from Microsoft and cyber security institutions. This article describes various modern cryptographic techniques that can be applied to the Windows operating system, including symmetric and asymmetric algorithms and end-to-end encryption. Protocol implementation security. This research also examines the effectiveness of cryptographic techniques in overcoming cyber security threats and provides the best recommendations for improving data security. It also provides a comparative analysis of various cryptographic techniques implemented in Windows operating systems. This study shows that evaluating encryption techniques can help overcome cyber threats and provide optimal solutions to improve data security. Data sources were obtained from academic journals, books, and technical documents from Microsoft and cyber security.